On the Stability of the Distribution of the Market Component in Stock Price Changes - Brenner, Menachem (Journal of Financial and Quantitative Analysis, 1974)
Stable distributions are suggested as being the underlying distributions for many economic variables. Capital market variables, in particular, are said to follow a member of the symmetric stable class.